Trans Fat Supplementation Increases UV‐Radiation‐Induced Oxidative Damage on Skin of Mice. Issue 10 (5th June 2013) - Barcelos, R. C. S.; Segat, H. J.; Benvegnú, D. M.; Trevizol, F.; Roversi, K.; Dolci, G. S.; Dias, V. T.; Piccolo, J.; Veit, J. C.; Emanuelli, T.; Bürger, M. E.
Abstract: We evaluated the influence of fish oil (FO, rich in n‐3 FA), soybean oil (SO, rich in n‐6 FA) and hydrogenated vegetable fat (HVF, rich in trans FA) on the oxidative status and viability of skin cells of mice exposed to ultraviolet radiation (UVR). Mice were supplemented with FO, SO or HVF for three months and exposed to UVR (2.72 mJ/cm 2 ) for 2 days. One day after the last UVR session, the FO group showed higher levels of n‐3 fatty acids (FA), while the HVF showed higher incorporation of trans FA (TFA) in dorsal skin. UVR increased lipid peroxidation and protein carbonyl levels of the HVF and to a lesser extent of the control and SO groups. Although all irradiated groups showed increased skin thickness, this increase was slighter in FO mice. UVR exposure reduced skin cell viability of the control, SO and HVF groups, while FO prevented this. Catalase activity was reduced independently of the supplementation and SOD level was increased in C and FO groups after UVR exposure; FO prevented the UVR‐induced increase in glutathione levels, which was observed in skin of the control, SO and HVF mice. Our results showed the beneficial effects of FO supplementation, as well as the harmful effects of trans FA, whose intensity can increase vulnerability to skin diseases.